Colonialité et occidentalocentrisme : quels enjeux pour la production des savoirs ? - Rachel Solomon Tsehaye; Henri Vieille-Grosjean (Recherches en Éducation)
This article deals with the power relations in the production of scientific knowledge, which highlights the imbrication of science and politics. It focuses on the existence and the influence of an ostracizing phenomenon that questions the universality claim in the science framework and scientific paradigms theorized in the (mainly Western) learned bodies. Adopting a reflexive and critique posture and using an inductive methodological approach and some elements from a literature review, the authors aim to shed light on the new forms of relevance attributed to the notion of coloniality. It provides a concept that may be enforced in the analysis of norms conflicts and social and cultural gaps. Il also constitutes an analytical grid of the hierarchy in the spread of knowledge and the subsistence of subaltern groups.